PENGARUH PEMBERIAN PAKAN TERHADAP PEMELIHARAAN IKAN NEMO (Amphiprion ocellaris) PADA SUHU YANG BERBEDA - Putri Dwi Aryanti; Nunik Cokrowati; Laily Fitriani Mulyani (Journal of Fish Nutrition, 2022)
Nemo fish (Amphiprion ocellaris) is an economic value ornamental fish with an attractive orange color characteristic with a unique white pattern with black stripes. The price of nemo fish with a size of 2-3 cm has a price ranging from Rp. 6,000-7,000. The purpose of this study was to determine the effect of the temperature of the rearing medium on the growth and survival of nemo fish (Amphiprion ocellaris). The research method used in this study is an experimental method using a completely randomized design (CRD) consisting of five treatments and three replications, namely A (23oC), B (26oC), C (29oC), D (32oC), and K (control following room temperature) so there are 15 experimental units. The results of this study were the highest daily growth rate was obtained at 2.11%, the highest absolute length growth was obtained at 1.04 cm, the best feed conversion ratio was obtained at 1.55 grams, and the highest survival rate was obtained at 93.33% in the treatment 32oC. The value of the water quality parameters pH ranged from 7.0 to 8.0, salinity ranged from 28-32 ppt, dissolved oxygen ranged from 5.0-10.0 mg/L, and ammonia <0.15 mg/L. The results of the Analysis of Variance (ANOVA) gave a significant effect and the results of Duncan's test gave a significantly different effect for all treatments. The conclusion of this study is that temperature has a significantly different effect on the growth and survival of nemo fish.